Predicting Risk of Incident Heart Failure Among Type 2 Diabetic Patients Using the WATCH-DM Risk Score - Sadiq, Mayasah A.; Salih, Alaa A.; Jamil, Najlaa Fawzi (International Journal of Membrane Science and Technology, 2023)
Background: The concomitant occurrence of type 2 diabetes mellitus and heart failure is common with increased mortality. WATCH-DM risk score is newly developed that assists heart failure prediction in the future five years. Objective: To predict the risk of heart failure among patients with type 2 diabetes mellitus in outpatient setting, using the novel WATC DM risk score. Methodology: Descriptive cross sectional study was applied involving a convenient sample of diabetic patients in single diabetic center in Baghdad over period of 1 year, where each one interviewed and asked about sociodemographic data, previous myocardial infarction and coronary artery bypass graft then Blood pressure measured, ( electrocardiography)ECG performed and the patient send for investigations need for WACH-DM risk scoring including fasting blood sugar, Serum Creatinine and HDL-C, risk score calculated for each patient according to the WACH–DM score. Results: The sample included 112 diabetic patients of who 81 (75%) of them were females, mean WATCH-DM score was 10.39±3.6 (mean± SD), very low score 26%, high score 24% and very high score 19%. Conclusion: Among study sample 43% of patients have high and very high risk score of incident heart failure using WATCH-DM risk score